The identification and classification of endogenous retroviruses in the horse genome - E, Batmagnai; Bongcam-Rudloff, Erik; Kent, Matthew Peter; Andersson, Göran (Mongolian Journal of Agricultural Sciences, 2018)
Endogenous retroviruses (ervs) are sequences that derived from ancient retroviral infections of germ cells and integrated in humans, mammals and other vertebrates millions years ago. These ervs are inherited according to Mendelian expectations as all other genes in the genome. Coding sequences are flanked by two ltrs (long terminal repeat sequences). Most ervs are defective however some ervs still have open reading frames in their genome. These ervs settle close to functional genes or within the genes and can influence or control functions of the host genes using their ltrs. Most integration has deleterious effects. However some integration could be example of positive co-adaptation as syncitin. The first equine endogenous beta retrovirus which is ecerv-beta1 has been found in 2011 by Antoinette C.van der Kuyl1. The first known beta retrovirus and few pol gene similar to foamy retrovirus were only known endogenous retroviruses fixed in the domestic horse (equuscaballus) genome. Our aim of the study was to identify other endogenous retrovirus sequences in an equine genome and classify them into groups. Based on the high number of sines (equine repetitive element) in the horse genome we hypothesized that certain ervs will be located sufficiently close to sines that they will be amplified using an unbiased sine-pcr approach with degenerate primers. The nearest sine element was located 5.5 kbp upstream at the 5’of the ecerv-beta1. Pan-pol pcr was also used to find novel ervs based on 640 bp long region of pol gene which is the most conserved region of ervs. 27 complete and novel ervs that are 13 beta, 13 gamma, 1 spuma and 249 candidate endogenous retroviruses have been revealed using ltr_struc tool and double checked by retrotector online tool and ncbi-blast tool. It was proven that ecerv-beta1, which has 2 ltrs with 1% divergence between ltrs has a polymorphism among 13 different breeds.